Editors’s Introduction to the Special Issue on "Grid, Cloud and Sky Applications for Knowledge-based Industries and Businesses" - Stankovski, Vlado; Petcu, Dana (Informatica)
Editors's Introduction to the Special Issue on "Grid, Cloud and Sky Applications for Knowledge-based Industries and Businesses"